Активність протеїнкіназ у цитозолі клітин слизової оболонки шлунка щурів за умов експериментальної виразки - Ковальова, В.А.; Гавриш, Л.І.; Остапченко, Л.І. (Видавничий дім "Академперіодика" НАН України, 2007)
The definition of the activity of protein kinases in cytosol of cells of mucosa under different experimental models of stomach ulcer has shown that only the activity of tyrosine kinase is increased. Thus, this enzyme is a sensitive link in the cascade of biochemical reactions under the development of the given pathological process.